Pengaruh Kemudahan dan Kelengkapan Fitur BSI Mobile Terhadap Kepuasan dan Loyalitas Nasabah - Ira Nur Alfiana; Muhtadin Amri (Department of Islamic Banking, 2023)
The purpose of this study was to analyze the effect of convenience and completeness of features on satisfaction and loyalty and whether satisfaction is able to mediate the effect of convenience and completeness of features on customer loyalty. This research is a quantitative study with a sample of 100 BSI customers using mobile banking with incidental sampling technique. Data was collected by distributing questionnaires to a sample of 100 customers. The data was analyzed using the partial least square (PLS) method. The results showed that: convenience has no effect on customer satisfaction and loyalty, feature completeness has a positive and significant effect on customer satisfaction and loyalty, satisfaction has a positive and significant effect on customer loyalty, and satisfaction is not able to mediate convenience to customer loyalty but is able to mediate feature completeness to customer loyalty. Based on the results of this study, Bank Syariah Indonesia is expected to continue to update the completeness of the features available on BSI Mobile so as to increase customer satisfaction and loyalty.